Evaluation of an Online Educational Intervention to Increase Knowledge and Self-efficacy in Disaster Responders and Critical Care Transporters Caring for Individuals with Developmental Disabilities. (3rd January 2019) - Edinger, Zachariah S.; Powers, Kelly A.; Jordan, Kathleen S.; Callaway, David W.
ABSTRACT: Objective: Disability-related education is essential for disaster responders and critical care transporters to ensure positive patient outcomes. This pilot study evaluated the effect of an online educational intervention on disaster responders and critical care transporters' knowledge of and feelings of self-efficacy about caring for individuals with developmental disabilities. Methods: A 1-group, pretest-posttest, quasi-experimental design was used. A convenience sample of 33 disaster responders and critical care transporters participated. Results: Of the 33 participants, only 24% had received prior education on this topic, and 88% stated that such education would be beneficial to their care of patients. Nineteen participants completed both the pretest and posttest, and overall performance on knowledge items improved from 66% correct to 81% correct. Self-efficacy for caring for developmentally disabled individuals improved, with all 10 items showing a statistically significant improvement. Conclusion: Online education is recommended to improve the knowledge and self-efficacy of disaster responders and critical care transporters who care for this vulnerable population after disasters and emergencies. ( Disaster Med Public Health Preparedness . 2019;13:677–681)